(untitled) (International Journal of Geoscience, Engineering and Technology, 2023)
In Brazil and in the world, beer is a popular and widely consumed drink. The optimization of some processes in the production of craft beers has been gaining prominence since it facilitates the process, providing more safety and quality in the final product. Therefore, the present work aims to increase the efficiency in the extraction of sugars, maintaining temperature stability during the process. For this, an adaptation of a brewing pot was carried out and the development of a controller that uses the Arduino platform together with different sensors. Furthermore, the man-machine interface was elaborated through the buttons, OLED display, buzzer and LEDS. The pot and the controller work together to control the entire process, keeping the wort temperature within the established ranges, during the time specified by the recipe. Throughout the development of the project, several tests were carried out to identify possible failures in the system. The controller was able to reach and control temperature steps, offering a viable and effective solution for beer production, in addition to being cost-effective.